Electronic Health Record Mid-Parental Height Auto-Calculator for Growth Assessment in Primary Care. (October 2016) - Lipman, Terri H.; Cousounis, Pamela; Grundmeier, Robert W.; Massey, James; Cucchiara, Andrew J.; Stallings, Virginia A.; Grimberg, Adda
Primary care providers are charged with distinguishing children with an underlying growth problem from those with healthy variant short stature. Knowing the heights of the biological parents aids in making that decision. This study sought to determine the feasibility and functionality of an electronic mid-parental height (MPH) auto-calculator in the clinical assessment of child growth in a pediatric primary care setting. Clinicians completed surveys for 62% of 6803 children (mean height 13 ± 7 percentile) with recorded parent heights. Collecting parent height data required <30 seconds in 91% of encounters. The MPH tool confirmed clinicians' initial growth assessment in 79% of cases and changed it in 4%; the remainder did not use the tool. Clinicians who changed assessment were more likely ( P < .0001) to pursue more comprehensive evaluation. The MPH tool was a quick, functional resource as a component of an electronic health record system in actual, busy, pediatric primary care practices.